2005
DOI: 10.1016/s0002-9440(10)62968-9
|View full text |Cite
|
Sign up to set email alerts
|

The Loss of Sarco/Endoplasmic Reticulum Calcium Transport ATPase 3 Expression Is an Early Event during the Multistep Process of Colon Carcinogenesis

Abstract: Calcium accumulation in the endoplasmic reticulum is accomplished by sarco/endoplasmic reticulum calcium transport ATPases (SERCA enzymes). To better characterize the role of SERCA3 in colon carcinogenesis, its expression has been investigated in colonic epithelium, benign lesions, adenomas, and adenocarcinomas. In addition, the regulation of SERCA3 expression was analyzed in the context of the adenomatous polyposis coli/␤-catenin/T-cell factor 4 (TCF4) pathway and of specificity protein 1 (Sp1)-like factordep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
116
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(125 citation statements)
references
References 74 publications
7
116
0
1
Order By: Relevance
“…In addition, marked induction of the expression of the SERCA3 endoplasmic reticulum Ca 2+ ATPases has been shown earlier during megakaryocytopoiesis [88], during cell differentiation in various leukemia [21,42] and gastric/ colon cancer cells ( [21,22,89]. When taken together with data shown on PMCA expression in our present work, these observations indicate that the remodeling of cellular Ca 2+ homeostasis during differentiation is a phenomenon that concerns Ca 2+ sequestration in the ER, as well as Ca 2+ extrusion across the plasma membrane.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, marked induction of the expression of the SERCA3 endoplasmic reticulum Ca 2+ ATPases has been shown earlier during megakaryocytopoiesis [88], during cell differentiation in various leukemia [21,42] and gastric/ colon cancer cells ( [21,22,89]. When taken together with data shown on PMCA expression in our present work, these observations indicate that the remodeling of cellular Ca 2+ homeostasis during differentiation is a phenomenon that concerns Ca 2+ sequestration in the ER, as well as Ca 2+ extrusion across the plasma membrane.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, such treatments can induce or enhance cell differentiation in Friend erythroleukemia cells [94], in myeloid leukemia [95] and colon cancer [89]. This indicates that modulation of cellular Ca 2+ homeostasis during differentiation is not a simple passive consequence of the differentiation process.…”
Section: Discussionmentioning
confidence: 99%
“…5D). Given that SERCA3 upregulation has been reported in cancer (Brouland et al, 2005), its expression was also investigated but found to be unchanged in cells lacking K-Ras G13D (supplementary material Fig. S1).…”
Section: G13dmentioning
confidence: 99%
“…10,11 SERCA mutations are associated with some cancers, [12][13][14] suggesting involvement in cell differentiation. 15 SERCA3 human mutations seem associated with type 2 diabetes. 16 Mouse SERCA2 knockouts are not viable at the homozygous state, but heterozygotes exhibit SERCA2a-type (defect in heart contractility and relaxation) 17 and SERCA2b-type defects, evocative of Darier syndrome.…”
Section: Introductionmentioning
confidence: 99%